2004
DOI: 10.1073/pnas.0408369102
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopic analysis of the binding of the Schizosaccharomyces pombe origin recognition complex and the spOrc4 protein with origin DNA

Abstract: In eukaryotes, the initiation of DNA replication requires the interaction between origin sequences and the origin recognition complex (ORC), which is highly conserved. In this report, atomic force microscopy (AFM) was used to examine the binding of Schizosaccharomyces pombe (sp) ORC and the spOrc4 protein with the sp autonomously replicating sequence 1 (ars1). AFM imaging revealed that spORC binding to ars1 occurred solely through spOrc4p and depended on the N-terminal AT-hook domains present in spOrc4p. At hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 31 publications
5
38
0
Order By: Relevance
“…30 Atomic force microscopy studies of the S. pombe ORC have suggested that approximately 150 bp of DNA are wrapped around the protein complex. 31 DNA wrapping of Ori binding proteins has been observed also with the Drosphila DmORC, 32 and this could explain the distance of 160 bp that (Fig. 5E).…”
mentioning
confidence: 79%
“…30 Atomic force microscopy studies of the S. pombe ORC have suggested that approximately 150 bp of DNA are wrapped around the protein complex. 31 DNA wrapping of Ori binding proteins has been observed also with the Drosphila DmORC, 32 and this could explain the distance of 160 bp that (Fig. 5E).…”
mentioning
confidence: 79%
“…One explanation for this discrepancy is that an additional, as yet unidentified, protein interacts at this location (Cayrou et al 2011). Alternatively, it has been shown for S. pombe (Gaczynska et al 2004) and Drosophila (Remus et al 2004) that following the initial binding, DNA is wrapped around the ORC complex, which could result in a distance of ∼160-190 bp between an initial ORC binding site and the location at which the CDT1-MCM2-7 complex is bound. Alternatively, MCM2-7 complex loading has been studied only on naked DNA substrates, and it is unclear whether these studies accurately reflect loading to chromatin.…”
Section: Dna Replication Origins and Genome Damagementioning
confidence: 99%
“…Many of the AAA+ domains within ORC and Cdc6 are linked to other modules, in particular a predicted variant of an HTH fold termed a winged-helix domain (WHD), which may be involved in DNA binding (4,84,93). The N terminus of S. pombe Orc4 is further decorated with several AT-hook repeats that promote interactions between the initiator complex and origin DNA (40,41,94), whereas the N terminus of Orc1 universally bears a conserved bromo-adjacent homology (BAH) domain implicated in binding multiple factors (50,95,96), including transcriptional silencing factors such as Sir1 (in yeast) and HP1 (in human and Drosophila) (97)(98)(99). The Orc1 BAH domain binds to nucleosomes, specifically recognizing dimethylated histone H4 tails (100).…”
Section: Eukaryotic Origin Recognition Complexmentioning
confidence: 99%